Shift Share Location Quotient, and ARIMA Forecasting Methods in the Analysis of the Competitiveness of Tual City and the Economic Growth of the Maluku Province. - La Adisamu, Nova prista; Endroyono, Endroyono; Nugroho, Sumpeno Mardi Susiki (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
Abstract— Economic development and high competitiveness are significant factors in a region’s success, especially since the enactment of Law Number 32 of 2004 on Regional Government, which converted the centralized to a decentralized system. This study analyzes the GRDP data of Tual City and Maluku Province using the shift share method and the Location Quotient method, resulting in a shift share assessment of Tual City’s regional competitiveness. It can be seen that the economic state of Tual City is still influenced by the Maluku Province’s economic growth of 593,688 with an overall slowdown in Proportional Shift of (-633.686) and an differential shift of (-5,756.040) during 9 years. The ARIMA forecasting method was then used to project the province’s 5th-year economic growth of 8,486,707 (billions) in the 5th period.